Trends in the Development of Digital Literacy-Based Learning Media For Indonesian Language Learning in Elementary Schools From 2020 to 2025 - Ayub Prastiyo; Sri Wardani; Bambang Subali; Nuni Widiarti (Journal of Innovation and Research in Primary Education, 2026)
The development of information technology in the last five years has led to a significant increase in the use of digital literacy-based learning media in elementary schools. This trend has strengthened since the COVID-19 pandemic, which forced the transformation of learning from conventional to digital. This article aims to examine the trend of developing digital literacy-based learning media in Indonesian language learning in elementary schools for the period 2020–2025. The writing method used is a systematic literature study of relevant national and international scientific articles. The results of the study show that since 2020, there has been a shift from the use of simple digital media such as PDF modules and learning videos to more interactive media such as Android-based applications, online learning platforms, and gamification media. In addition, the trend of integrating digital literacy into Indonesian language learning not only improves students' basic literacy skills but also encourages active engagement, collaboration, and creativity. However, several challenges remain, such as the technology access gap, limited teacher competence, and lack of integration with the local cultural context. The conclusion drawn from this paper is that the trend of developing digital literacy-based learning media needs to be directed towards a more innovative, inclusive, and sustainable approach in order to support the quality of Indonesian language learning in elementary schools.